Case report: Basal cell carcinoma arising within the nevus sebaceous: report of 4 cases and literature review - Lei, Tianbing; Lu, Yonghong; Feng, Yanyan; Ni, Yao (Frontiers in Oncology, 2025)
Nevus sebaceous (NS) is a congenital hamartoma characterized by the presence of skin structures, including the epidermis, sebaceous glands, and hair follicles. NS predominantly occurs on the scalp and has the potential to give rise to secondary tumors, with a small proportion being malignant; the most frequently observed malignant tumor associated with NS is basal cell carcinoma. In this report, we retrospectively present four cases of sebaceous nevus on the scalp complicated by basal cell carcinoma. The pathological diagnoses were unequivocal in all four patients, who exhibited typical clinical manifestations, with all cases localized to the left parietotemporal region of the scalp. The etiology of NS may be linked to genetic mutations or ultraviolet exposure. Treatment options vary, with surgical resection likely being the most common method of eradication.